Penerapan Metode Triple Exponential Smoothing Pada Sistem Prediksi Keuntungan Bisnis Ayam Broiler Guna Meningkatkan Pengelolaan Keuangan Peternak - Dine Tiara Kusuma; Muhammad Farid Rifai; M Yoga Sudirman (KILAT, 2019)
Profitable business predictions are used to help chicken breeder in anticipating profit earned in the next harvest. The existence of a profitable prediction, enables breeder to predict when the next harvest is experiencing little profit or harvest failures. In addition, to be the breeder still has risky capital and bankruptcy. In this research, the author compare two methods accordingly in this case, there are triple exponential smoothing method and monte carlo method. The data used in the calculation of news data is profitable on the previous harvest. To find the value of two methods are match, the author's use mean absolute percentage error (MAPE) to learn the percentage of the value of the error. Based on the value of MAPE, triple exponential smoothing method have value of 12.10% with α value = 0.3 and monte carlo method have value of 40.58%. Meanwhile with the anticipated value of profit testing for the next 2 harvest grab the difference up to Rp. 19,935,410.